Analisis Deskriptif Penggunaan 「 ~タばかり」、「~タところ」、「~タとたん」 yang Menyatakan Beberapa Saat Waktu yang Sudah Berlalu Setelah Suatu Aktivitas Terjadi - Asep Achmad Muhlisian (IZUMI, 2013)
ABSTRACT This study aimstoseeany difference in meaning, functionanduse ina sentenceforthe wordorsentencepatternsof thepast tense verb~tacontainingthe sameorsynonymousterms, namely: 「~ タばかり」, 「~ タところ」, and「~ タとたん」stating a few momentsof timethat haselapsedaftertheactivityoccurred. Descriptivemethodsusedtocollect datausing thesevenpieces of datasourceJapanesedictionary. The results showedthattheunderstandingthoughlooks similar, butthere are also differences. Asa function of time, the result, theparticlesfollowandfeel ofthesentence, thethirdpatternhasa prettycleardistinction. (Key Words). Past verb (doushi) , Synonym, Bakari, Tokoro, Totan.